Оценка индивидуального риска от наиболее распространенных потенциально опасных объектов - Il'yushonok, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Risk assessment methodology is discussed for hazards created by petrol filling stations, ammonia refrigeration facilities, liquefied hydrocarbon gas installations, and chlorine storages. Risk is determined by the product of accident probability and of extent of damage. The probability is evaluated from the object structure and logic of accident development. On the basis of data on equipment components failures and possible accident scenarios, risks for the groups of objects under consideration are estimated.